Analyzing Risk Factors for Brain Damages in a Group of Newborns with High Risk of Neurodevelopmental Sequelae: A Moroccan Study - S. Ait Malk; MA. Radouani; Y. Taboz,; H Benkirane; H Aguenaou; HM Mrabet; Amina Barkat (Journal of Educational, Health and Community Psychology, 2016)
Abstract The aim of the study is to identify risk factors for occurrence of perinatal brain injury objectified in transfontanellar ultrasound (TFU) in a group of infants with high risk of neurodevelopmental sequelae. It’s a retrospective study, conducted at the neonatal intensive care unit of the Children's Hospital of Rabat, during the period from 1 January to 31 December 2014. Were included newborns hospitalized for a medical condition with intrauterine croissance retardation (ICUR) more than 5 days and have survived. The neurological workup includes TFU made between day 2 and day 5 of life. Data analysis was performed on SPSS 18.0 software. The level of significance was p <0.05.  The percentage of newborns that developed neurological damage to the TFU was 36%. Patients with abnormalities in the TFU had a breakdown time, duration dependence of O2, duration of hospitalization and a higher frequency of nosocomial infections than patients without abnormality. The interest in the prevention of nosocomial infections is to try to shorten the duration of invasive ventilation, favoring fast relay noninvasive ventilation. Keywords: brain injury; newborns; prematurity, neurodevelopmental sequelae, trans-fontanellar ultrasound.